WORD FORMATION PROCESSES IN THE JARGONS FOUND IN WORLD BEATBOX COMMUNITY WEBSITE HUMANBEATBOX.COM - HAIKAL, FIKRI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: word formation processes, beatbox jargon. Jargon can be categorized as new words. Media like radio, television, magazine, newspaper, tabloid, and advertisement have a big role in developing new words. Then, those new words become popular in daily communication. As new words are formed, there will be a process forming the words which is word formation process. In this research, the writer focuses in analyzing the word formation processes and the meaning of beatbox jargons found in World Beatbox Community website humanbeatbox.com. There are three problems of this study, they are (1) What are the jargons found in World Beatbox Community Website humanbeatbox.com? (2) What are the meaning of the jargons found in World Beatbox Community Website humanbeatbox.com? (3) What are the word formation processes of the jargons found in World Beatbox Community Website humanbeatbox.com? The writer uses descriptive qualitative research to analyze the types of word formation processes conveyed in the articles of World Beatbox Community website humanbeatbox.com. The writer uses Yule’s theory (2006). The writer validates the data by sending email to some experts in order to get more information about the beatbox jargons and to make the data credible and dependable.In this study, the writer finds 35 (thirty five) beatbox jargons in World Beatbox Community website humanbeatbox.com. The result of this study shows that there are seven of ten word formation processes used in forming the jargons; they are coinage, borrowing, compounding, blending, clipping, backformation, conversion, acronyms, derivation, and multiple processes.The writer suggests further researchers study word formation process and analyze all articles in World Beatbox Community website humanbeatbox.com or other beatbox website, therefore the beatbox jargons can be seen in other type of word formation processes.